A prospective study on the long‐term outcome of prepubertal and pubertal boys undergoing testicular biopsy for fertility preservation prior to hematologic stem cell transplantation. Issue 9 (10th July 2020) - Borgström, Birgit; Fridström, Margareta; Gustafsson, Britt; Ljungman, Per; Rodriguez‐Wallberg, Kenny A.
Abstract: Background: Few studies have reported the long‐term outcomes of prepubertal and pubertal boys undergoing testicular biopsy for fertility preservation (FP). Procedure: This prospective longitudinal study examined 21 boys (aged 1.5‐14.5 years) who underwent testicular biopsy for FP prior to allogeneic (n = 20) or autologous (n = 1) hematological stem cell transplantation (HSCT) between 2003 and 2010. During counseling, pubertal boys were encouraged to produce a sperm sample by masturbation, while prepubertal boys were presented with surgical testicular tissue retrieval as an option for experimental FP. Clinical outcomes included postoperative complications, pubertal development, and sex‐hormone levels. Survivors approaching adulthood were encouraged to provide semen samples. Results: Twenty boys, including 14 in prepuberty and six in early puberty (Tanner stage 2‐3), underwent open testicular biopsies. Two pubertal biopsies contained mature sperms, which were cryopreserved. Testicular tissue was vitrified in the remaining 18 cases. One pubertal boy (Tanner stage 4) underwent percutaneous testicular sperm aspiration and sperms obtained were cryopreserved. Postoperative complications (hematoma or infection) were rare. Overall, 14 boys survived >5 years (mean follow‐up after HSCT, 7.2 years) and 11 showed advanced puberty. Semen samples were provided by five boys and obtained sperm were cryopreserved from two. Individuals at adulthood had normal testosterone levels but subnormal testicular size, high follicle stimulating hormone, and low inhibin B and anti‐Müllerian hormone levels. Conclusion: No long‐term risks were detected during continuous clinical follow‐up. Experimental testicular biopsies for FP were well accepted by the patients and families, despite the absence of methods to use prepubertal tissue for fertility treatment.